Perumusan dan Pengembangan Tujuan Instruksional Khusus di SDN Sarakan 2 - Ina Magdalena; Tasya Farlidya; Winda Yuniar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
This study aims to determine the writing of specific instructional objectives at SDN SARAKAN 2. The method that will be used at the time of research is descriptives method through a qualitative approach. The object to be studied is a grade 3 teacher at SDN SARAKAN 2. The process to be used at this time is interview and documentation techniques. The formulation of specific learning objectives includes only learners and behavior. The teaching method in genral the teacher applies the lecture method using the powerpoint slide media which takes place when online learning begins and online question and answer wuestions are the given online and the assignment is collected. Special instructional management is manidested in the presence of a coordinator who is responsible for equipment and supplies such as primary school teachers or commonly referred to as homeroom teachers, who have design favtors, namely: 1) Espertise in designing online-based learning; 2) Realization of teacher training; 3) The skill of applying concepts to new situations in different ways; 4) Make the school a learning organization; 5) The school is able to manage in planning, organizing, coordinating and supervising; 6) The ability to solve problems with systematic step in learning; 7) Skill to elaborate and evaluate learning outcomes.